Influence of environmental enrichment on the rehabilitation of white-eyed parakeet (Psittacara leucophthalmus) (Research, Society and Development, 2021)
The use of sensory, physical, cognitive, and alimentary stimuli are varieties of environmental enrichment used to minimize stress caused by the monotonous captive environment. The objective of this study was to verify the impact of environmental enrichment in escape-related behavioral stereotypies. Thirty birds of the species Psittacara leucophthalmus were observed from March to September 2016, received at the Wild Animal Recovery and Screening Center of the São Paulo State University (UNESP), School of the Veterinary Medicine campus Araçatuba. The methodology used for the behavioral observations was the focal animal with observation through filming were made by 18 hours per bird for three consecutive days, while physical, cognitive, food, and sensory enrichment methods were applied, and the assessment was carried out before, during, and after the application of environmental enrichment. The data were analyzed by the Shapiro-Wilk test for normality and by the Friedman test, which showed no significant difference (p >0.05) before, during, and after environmental enrichment. Despite the statistical analyses, the perception of the bird’s welfare improving was visually clear.